My Indonesia is Rich in Culture: Problem-based Articulate Storyline on Social Sciences Lesson Content - Ariadiny, Farah; Bektiningsih, Kurniana (Journal of Education Reseach and Evaluation, 2023)
Natural and social science is content of lessons that require memorization. Therefore, in delivering material, it is necessary to use tools that can increase the success of the teaching and learning process. Articulate Storyline is one of the popular e-learning software and has several advantages that make it a good choice in developing interactive learning content. Articulate storyline has an intuitive and easy-to-use interface, enabling users to create interactive learning content without having a strong programming or graphic design background. This makes it very suitable for teachers, instructors, and learning designers. The aim of this study is to develop Articulate Storyline media based on problem-based learning in fourth grade in science content. The research method used is Research and Development (R&D) based on ADDIE research. The data collection techniques used are test and non-test. Meanwhile, the data analysis technique used is qualitative and quantitative data analysis. The research results show that the Articulate Storyline media is very suitable for use with a percentage of material experts of 92% and media experts of 91%. Meanwhile, the effectiveness of using Articulate Storyline media in learning activities was stated to be quite effective based on an average increase (n-gain) in student learning outcomes of 0.61 and an increase in the average pre-test score of 58 to 84 during the post-test. From these results, it can be concluded that problem-based learning-based Articulate Storyline media is very feasible and quite effective for use in fourth grade Science learning.